1993
DOI: 10.1063/1.464399
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy vibrational modes of the monolayer adsorbate CO2/NaCl(001)

Abstract: Dispersion curves of surface vibrational modes of monolayer CO2/NaCl(001) have been measured by inelastic He atom scattering along the ΓX azimuth. Eight phonon modes could be followed across almost the entire Brillouin zone. The identification of the modes is discussed based on previously calculated normal mode energies at the zone origin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1995
1995
2002
2002

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Similar dispersionless adsorbate phonon modes have been observed previously for a number of other monolayer systems. 6,25 In spite of the lack of sufficient signal to determine any dispersion of the E 2 mode, it is also tentatively assigned to some form of frustrated adsorbate vibrational motions. Additional information on the identities of these modes is provided by TOF measurements on the corresponding C 2 D 2 adlayer.…”
Section: Inelastic Helium Atom Scattering Resultsmentioning
confidence: 99%
“…Similar dispersionless adsorbate phonon modes have been observed previously for a number of other monolayer systems. 6,25 In spite of the lack of sufficient signal to determine any dispersion of the E 2 mode, it is also tentatively assigned to some form of frustrated adsorbate vibrational motions. Additional information on the identities of these modes is provided by TOF measurements on the corresponding C 2 D 2 adlayer.…”
Section: Inelastic Helium Atom Scattering Resultsmentioning
confidence: 99%
“…Both the several distinct environments for the molecules in that structure and its higher density lead to the expectation that there would be considerable dispersion as seen, for example, with CO 2 on NaCl. 18 Finally, various models of the physisorption potentials were assessed. Large contributions to the energy were found to arise from the interaction of the distributed molecular charge distributions with the very nonuniform electrostatic fields at the surface of the NaCl crystal.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the HAS angular distributions from the NaCl films exhibit significantly lower diffraction peak intensities as well as higher background intensity levels for any mode of film preparation ͑different crystal temperatures during the film deposition, different annealing time, and temperatures, etc.͒. Although, earlier experiments with other adsorbates showed good agreement between the HAS and the LEED data 18,57 we conjecture that the situation may differ for water, since water adsorption on surfaces is anticipated to depend strongly on the defect structure of the substrate. For example, in related experiments on water adsorption on the Cu͑111͒ surface Hinch and Dubois 58 demonstrated that two phases of water ͑metastable and stable͒ can be formed depending on the defect concentration consisting of steps or contaminants.…”
Section: ͑3͒mentioning
confidence: 92%
See 1 more Smart Citation
“…19) qv so that we again arrive at (A 1.13). Thus, the infinitesimal imaginary addition at the pole of the GF (A1.15) really arises from the theta-function in Eq.…”
Section: Gg(o))= \Co -O)g V Jmentioning
confidence: 94%